2015
DOI: 10.1074/jbc.m115.646315
|View full text |Cite
|
Sign up to set email alerts
|

Ctr9, a Protein in the Transcription Complex Paf1, Regulates Dopamine Transporter Activity at the Plasma Membrane

Abstract: Background:The dopamine transporter controls the concentration of dopamine at the synapse. Results: Ctr9, formerly identified as a nuclei protein, interacts with the dopamine transporter in the cytoplasmic compartment. Conclusion: This interaction facilitates the targeting of the dopamine transporter to the plasma membrane and increases its activity. Significance: Identifying the complete dopamine transporter interactome is essential to understanding how neurotransmission is regulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…We investigated whether DAT and snapin transcripts are coexpressed in neurons using double-labeling fluorescent insitu hybridization (FISH). As previously described (De Gois et al, 2015;Giros et al, 1991), DAT expression is restricted to the SNc and the ventral tegmental area (VTA), whereas snapin expression profile is more ubiquitous (Figure 2a and Supplementary Figure S2a). At high magnification, we observed that snapin and DAT transcripts are coexpressed in neurons of the SNc and VTA (Figure 2a).…”
Section: Coexpression and Colocalization Of Dat And Snapinsupporting
confidence: 64%
See 3 more Smart Citations
“…We investigated whether DAT and snapin transcripts are coexpressed in neurons using double-labeling fluorescent insitu hybridization (FISH). As previously described (De Gois et al, 2015;Giros et al, 1991), DAT expression is restricted to the SNc and the ventral tegmental area (VTA), whereas snapin expression profile is more ubiquitous (Figure 2a and Supplementary Figure S2a). At high magnification, we observed that snapin and DAT transcripts are coexpressed in neurons of the SNc and VTA (Figure 2a).…”
Section: Coexpression and Colocalization Of Dat And Snapinsupporting
confidence: 64%
“…This suggests that mutants that cannot bind snapin are not correctly exported to the membrane, again reinforcing the hypothesis that snapin has a role in DAT trafficking. Other studies identifying the molecular determinants regulating transporter trafficking and interactions with other proteins have focused on domains in DAT-CT others than the one identified in our study: the PDZ domain (Rickhag et al, 2013;Torres et al, 2001), residues 612-617 flanking the PDZ domain (Bjerggaard et al, 2004;Fog et al, 2006), and the initial residues before C580 (Carneiro et al, 2002;De Gois et al, 2015).…”
Section: Role Of Snapin In Dat Regulationmentioning
confidence: 88%
See 2 more Smart Citations
“…The role of the SH2 domain of CTR9 in nuclear localization has also been demonstrated, which confirms that CTR9 localization is not restricted to the nucleus, as its function has been primarily illustrated in the transcription complex Paf1. Thus, the recent research indicates that CTR9 modulates DAT function by regulating its trafficking [29].…”
Section: Significance Of Ctr9mentioning
confidence: 99%